THE INFLUENCE OF MEDIA AND POP CULTURE ON LANGUAGE CHANGE AND LANGUAGE VARIATION - Durdona Bahodirovna BOLTAYEVA (TADQIQOTLAR.UZ, 2024)
Abstract This work is about the influence of media and pop culture on language. Music, movies/TV,  fashion,  food,  and  arguably  even  more  important:  language,  ethics, politics, technology, and religion—be them theistic, atheist, gnostic, or whatever other inherent attributes one wants to establish.